Cryoablation reshapes the immune microenvironment in the distal tumor and enhances the anti-tumor immunity - Wu, Ying; Cao, Fei; Zhou, Danyang; Chen, Shuanggang; Qi, Han; Huang, Tao; Tan, Hongtong; Shen, Lujun; Fan, Weijun (Frontiers in Immunology, 2022)
As one of the local treatments, cryoablation plays an increasingly important role in the comprehensive treatment of malignant tumors with its advantages of less trauma, high reproducibility, and minimally invasive. Activation of anti-tumor immunity, another characteristic of cryoablation, has attracted more and more attention with the extensive application of immunotherapy. Unfortunately, the mechanism by which cryoablation enhances anti-tumor immunity is still unclear. In this study, we applied a multi-omics approach to investigate the effects of local cryoablation in the distal tumor microenvironment. The results revealed that large amounts of tumor antigens were released post-cryoablation, leading to a sterile inflammatory response in distant tumors. During this period, lysosome-related pathways were activated, resulting in overexpression of SNAP23 (Synaptosome associated protein 23) and STXBP2 (Syntaxin binding protein 2), activation of immune effector cells, suppression of the release of immunosuppressive factors, and finally enhancement of anti-tumor immunity. Finally, cryoablation turns “Cold tumors” into “Hot tumors”, which shows a broad prospect in the combined immunotherapy.